Role of Ion Dynamics in Electron‐Only Magnetic Reconnection - Yundan Guan; Quanming Lu; San Lu; Yukang Shu; Rongsheng Wang (Geophysical Research Letters)
Abstract Standard magnetic reconnection couples with both ions and electrons on different scales. Recently, a new type of magnetic reconnection, electron‐only reconnection without the coupling of ions, has been observed in various plasma environments. Standard reconnection typically has a reconnection outflow velocity of about one Alfvén speed. According to the scaling analysis, the electron outflow velocity is expected to be about one electron Alfvén speed in electron‐only reconnection. However, observations and simulations both find that the electron outflows are much slower than the electron Alfvén speed. In this letter, by performing two‐dimensional particle‐in‐cell simulations, we show that this is because ions play a role in electron‐only reconnection. The ions move slower than the electrons in the outflow direction, and such charge separation forms an in‐plane Hall electric field, which prevents the electrons from being accelerated to the electron Alfvén speed in electron‐only reconnection.